2016
DOI: 10.1186/s12936-016-1631-9
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of malaria reactive case detection in an area of low and unstable transmission on the Myanmar–Thailand border

Abstract: BackgroundReactive case detection is an approach that has been proposed as a tool for malaria elimination in low-transmission settings. It is an intuitively justified approach based on the concept of space–time clustering of malaria cases. When an index malaria clinical case is detected, it triggers reactive screening and treatment in the index house and neighbouring houses. However, the efficacy of this approach at varying screening radii and malaria prevalence remains ill defined.MethodsData were obtained fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 27 publications
(28 reference statements)
1
47
2
Order By: Relevance
“…RCD with antimalarial drugs has previously been shown to have only a minimal or moderate impact on reaching elimination (31)(32)(33)(34). Post-elimination, we find that RCD can help sustain a near-eliminated state, but only under certain performance criteria.…”
Section: Discussionmentioning
confidence: 59%
“…RCD with antimalarial drugs has previously been shown to have only a minimal or moderate impact on reaching elimination (31)(32)(33)(34). Post-elimination, we find that RCD can help sustain a near-eliminated state, but only under certain performance criteria.…”
Section: Discussionmentioning
confidence: 59%
“…A survey in coastal Kenya found that asymptomatic and symptomatic infections do not necessarily overlap spatially, and that clusters of symptomatic infections have greater temporal stability over more than ten years [42]. Another issue often highlighted is the different criteria and screening radii employed by countries to define and recruit neighbouring households [42] For example, RCD data from four villages in the Myanmar-Thailand border determined that RCD would only be successful at a radius of 150 metres, and any screening occurring beyond this radius would not perform better than random screening [2]. Another study in Pailin Province in western Cambodia screened the nearest five households for every fifteenth index case and ten nearest households for every 30 th index case.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of RCD ultimately depends on the number of cases found and treated in a timely manner and the resources allocated during implementation [2]. However, it is important to consider the added value of a tailored RCD approach based on demographic and ecological risk factors and more sensitive diagnostic tools to fully reap the benefits of this screening method to achieve malaria elimination [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, vector control activities including IRS and LLINs are intensified. RACD has been implemented in Africa and Asia with mixed results [110,[181][182][183][184][185][186]. Nevertheless, RACD provides an opportunity for public health workers to concurrently assess coverage of malaria interventions including LLINs, and should be advocated and practised.…”
Section: Towards Malaria Elimination -A Leap Forwardmentioning
confidence: 99%